2017
DOI: 10.1155/2017/9819350
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Compound “Jiedu Huayu” Reduces Liver Injury in Rats via Regulation of IL‐2, TLR4, and PCNA Expression Levels

Abstract: Aim of the Study. To investigate the preventative effects of Jiedu Huayu (JDHY) on D-galactosamine (D-GalN) and lipopolysaccharide-induced acute liver failure (ALF) and to evaluate the possible mechanisms of action. Materials and Methods. ALF was induced in Wistar rats by administrating D-GalN (900 mg/kg) and lipopolysaccharide (10 μg/kg). After treatment with JDHY granules, the levels of blood alanine aminotransferase, aspartate aminotransferase, total bilirubin, and prothrombin time were determined. Prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The role of GA, SY or GA and SY in hepatic regeneration was investigated by detecting the expression of PCNA mRNA and immunostained antibody. Commonly, upregulation of PCNA can increase the survival rate of cells and directly accelerates the DNA replication and cell proliferation (Paunesku and others ; Domitrović and others ).This study showed that GA and SY combination stimulate hepatic regeneration by overexpression of PCNA, this result confirmed by others (Huang and others ; Wang and others ).…”
Section: Discussionsupporting
confidence: 89%
“…The role of GA, SY or GA and SY in hepatic regeneration was investigated by detecting the expression of PCNA mRNA and immunostained antibody. Commonly, upregulation of PCNA can increase the survival rate of cells and directly accelerates the DNA replication and cell proliferation (Paunesku and others ; Domitrović and others ).This study showed that GA and SY combination stimulate hepatic regeneration by overexpression of PCNA, this result confirmed by others (Huang and others ; Wang and others ).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the level of IL-6 and TNF-a was lower in EHF group compared to the model group, suggesting that EHF could exert anti-inflammatory effect in the treatment of DN. Moreover, proliferating cell nuclear antigen (PCNA) is closely related to the synthesis of DNA and plays an important role in the initiation of cell proliferation (Summary, 2017). In this manuscript, PCNA protein level was strongly suppressed by EHF, representing the anti-proliferative effect of EHF.…”
Section: Discussionmentioning
confidence: 76%
“…Jie-Du-Hua-Yu (JDHY) granule is a traditional Chinese herbal compound, which has been used for over two decades in the treatment of liver diseases. This formula consists of six herbs: Radix paeoniae rubrathe, Artemisia capillaris, Rheum officinale, Radix curcumae, Oldenlandia diffusa, and Acorus gramineus 7,8. Our previous clinical studies suggested that JDHY exhibited protective effect in hepatitis B-related ALF patients and improved liver function 9.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanism was poorly understood. Based on previous reports on the beneficial activities of JDHY,7 we hypothesized that JDHY may attenuate LPS-induced liver injury in animal studies. To clarify its protective mechanism, we analyzed the effects of JDHY on LPS-induced damage both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%